2004
DOI: 10.1196/annals.1302.016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Fiber Orientation and the Left‐Right Asymmetry Determining Mechanism

Abstract: The invariant nature of body situs within and across vertebrate species implies that a highly conserved pathway controls the specification of the left-right (L/R) axis. Situs-specific morphogenesis begins at the end of this pathway and leads to normal organ arrangement, also known as situs solitus. Occasionally, individuals have a complete, mirror image reversal of this asymmetry, called situs inversus totalis (SIT). In these individuals, gross anatomy is mirror imaged. However, the helical myofiber pattern wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
4
10
0
Order By: Relevance
“…In the present contribution, it is shown that the helical arrangement of Torrent-Guasp's ventricular myocardial band model does not reflect the changes in configuration of the embryonic heart loop. This fact seems to be in accord with data from a recent study on situs inversus hearts suggesting that the definitive sense of twist of the helically arranged ventricular muscle fibres does not depend on the chirality (left-or right-handed) of the embryonic heart loop [31]. The ontogenetic evolution of the definitive structural and functional organization of the ventricular myocardial mass, therefore, most likely starts in the post-looping embryonic heart.…”
Section: Discussionsupporting
confidence: 88%
“…In the present contribution, it is shown that the helical arrangement of Torrent-Guasp's ventricular myocardial band model does not reflect the changes in configuration of the embryonic heart loop. This fact seems to be in accord with data from a recent study on situs inversus hearts suggesting that the definitive sense of twist of the helically arranged ventricular muscle fibres does not depend on the chirality (left-or right-handed) of the embryonic heart loop [31]. The ontogenetic evolution of the definitive structural and functional organization of the ventricular myocardial mass, therefore, most likely starts in the post-looping embryonic heart.…”
Section: Discussionsupporting
confidence: 88%
“…For example, in congenital anomalies, such as situs inversus totalis, the orientation of the apical and epicardial basal fibers is normal, but the orientation of the deeper endocardial basal fibers is inverted. 24 Twist is, thus, normal at the apex, but changes direction at the base, 25,26 causing absence of relative apex to base rotation. 26 Similarly, in patients with LV noncompaction and hypoplastic hearts, the absence of normal fiber architecture causes both the LV base and apex to rotate in the same direction, exhibiting none or minimal twist, a physical type of rotation that is called rigid body rotation.…”
Section: Impact Of Myocardial Structuralmentioning
confidence: 99%
“…Interestingly, individuals who have all organs arranged in a mirror-image pattern (situs inversus) generally face no adverse physiological consequences. However, cardiac muscle fiber architecture in these people is reversed only in the basal region of the left ventricle, leading to abnormal (not just reversed) torsion during the cardiac cycle (Delhaas et al, 2004). In contrast, serious malformations may result if the heart is the only organ that is reversed (dextrocardia).…”
Section: Studies Of Looping Directionalitymentioning
confidence: 99%